2021
DOI: 10.7150/ijms.53899
|View full text |Cite
|
Sign up to set email alerts
|

Exercise combined with trimetazidine improves anti-fatal stress capacity through enhancing autophagy and heat shock protein 70 of myocardium in mice

Abstract: Background: Anti-stress capacity is important to resist the occurrence of adverse events. To observe the effects of exercise, trimetazidine alone or combined on the anti-stress capacity of mice, and further explore its potential mechanism. Methods: Forty-four C57BL/6 male mice aged 8 weeks were randomly divided into four groups (n=11 for each group): control group (group C), exercise group (group E), trimetazidine group (group T), exercise combined with trimetazidine group (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The HFD+EX group was subjected to moderate-intensity swim training. 24 In brief, an adaptive training protocol was employed; mice were placed in a Morris water maze pool (XR-XM101-R, ZSdichuang, Beijing, China, with a diameter of 120 cm and a depth of 60 cm) and swam for 10 min on the first day. Thereafter, this was increased 10 min daily until 60 min/day.…”
Section: Methodsmentioning
confidence: 99%
“…The HFD+EX group was subjected to moderate-intensity swim training. 24 In brief, an adaptive training protocol was employed; mice were placed in a Morris water maze pool (XR-XM101-R, ZSdichuang, Beijing, China, with a diameter of 120 cm and a depth of 60 cm) and swam for 10 min on the first day. Thereafter, this was increased 10 min daily until 60 min/day.…”
Section: Methodsmentioning
confidence: 99%
“…35 Long-term exercise instigates benign changes in cardiac muscle autophagy and thus delays pathological remodeling to protect myocardial structure and function. By pre-implemented 5 weeks of aerobic exercise training on myocardial ischemia-reperfusion mice, Jiang et al 36 showed that exercise alleviated myocardial injury caused by ischemia-reperfusion and increased the expression of autophagy-related proteins BNIP3, LC3-II, and heat shock protein HSP70. These data indicated that exercise increased myocardial autophagy levels and enhanced the anti-stress capacity of mice.…”
Section: Exercise-mediated Autophagy In Cardiovascular Diseasesmentioning
confidence: 99%
“…For IR or diabetic patients, the survival rate and prognosis of acute stress including myocardial infarction, are poor 1 , 2 , which indicates that cardiac anti-stress capacity is impaired by IR. In our previous research, we found that autophagy, heat shock protein 70 (HSP70), and mitochondrial quality control were found to be vital in anti-fatal stress capacity in healthy mice 3 5 .…”
Section: Introductionmentioning
confidence: 99%